2009
DOI: 10.1063/1.3257915
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Lax pairs from non-ultra-local Poisson algebras

Abstract: We consider non-ultra local linear Poisson algebras on a continuous line . Suitable combinations of representations of these algebras yield representations of novel generalized linear Poisson algebras or "boundary" extensions. They are parametrized by a "boundary" scalar matrix and depend in addition on the choice of an antiautomorphism. The new algebras are the classical-linear counterparts of known quadratic quantum boundary algebras. For any choice of parameters the non-ultra local contribution of the origi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(30 reference statements)
0
9
0
1
Order By: Relevance
“…It is shown that the presence of special boundary terms suitably breaks the symmetry of the models under consideration, as also happens in discrete integrable models (see e.g. [5,8,27]).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is shown that the presence of special boundary terms suitably breaks the symmetry of the models under consideration, as also happens in discrete integrable models (see e.g. [5,8,27]).…”
Section: Discussionmentioning
confidence: 98%
“…i,j P 0i P 0j → dx dy P 0 (x)P 0 (y). (7.5) The modified monodromy matrix as well as the B, P matrices may be expressed as The entries T kl of the matrix are the non-local charges, which are realizations of the classical reflection algebra (3.3), (see also [27]). In particular, the continuum non-local charges emerging from (7.4) via (7.5) become: Consider now the continuum expression for T with T given in (5.10), and take into account that for the L-L model…”
Section: Boundary Symmetriesmentioning
confidence: 99%
“…Now we have to note that another class of Poisson-type algebras similar to the one of graded Poisson algebras of degree z 0 in Definition 1 but replacing the group Z by Z 2 has been considered in the literature. This kind of algebras are known as even and odd Poisson superalgebras, depending on taking degree0 or degree1, being of interest in studying, for instance, two-dimensional supergravity and three-dimensional systems ( [2,11,14,23]). However, as we know, there is not a category in the literature which allows us to combine a graded bracket of degree g 0 ∈ G and a graded commutative associative product via a graded Leibniz identity when the group G is an arbitrary abelian group.…”
Section: Definitionmentioning
confidence: 99%
“…As another example, we note that it is possible to recover Hamiltonian mechanics from the coordinate space of the theory by making use of graded Poisson algebras ( [20]). We can enumerate many more applications (see [2,14,15,18,23]), but we refer to [10] to a good review on this matter. Definition 1.…”
Section: Introductionmentioning
confidence: 99%
“…We also note that the interest on gradings on different classes of algebras has been remarkable in the last years, specially motivated by their applications in physics and geometry, see for instance [5,9,12,13,14,16,21]. Now recall that a Poisson algebra is an associative algebra endowed with a Lie product, denoted by {•, •}, in such a way that the Lie and the associative products are compatible via the Leibniz identity {x, yz} = {x, y}z + y{x, z} for any x, y, z ∈ P (see [1,4,17,18]). Also recall that the context of strong graduation has been extensively considered in the literature (see for instance the text book [20] or the recent reference [15,22,23]).…”
Section: Introduction and Previous Definitionsmentioning
confidence: 99%